俄中北極戰略之比較研究 - 郭大維; Kuo, Ta-Wei (2023)
碩士 國立政治大學 俄羅斯研究所 110263008 隨著溫室效應的加劇，世界正在迎接著前所未有的新氣候。隨著北極海冰的逐年消融，意味著北冰洋將可能在2040至2060年間完全通航，其連帶顯露出的巨大地緣政治價值自然是國家行為者難以忽視的新現實。千禧年後，各國逐漸意識到北極巨大的地緣政治驅動力，不僅北極國家大力地開發北極，非北極國家也試圖參與北極事務，使得北極議題與北極事務的政治重要性逐漸上升。\n本文之目的，是以地緣政治理論為出發點，深入比較俄羅斯聯邦與中華人民共和國北極戰略的異同。俄羅斯與中國，作為北極與非北極國家，分別頒布了一系列的國家北極政策，並積極地開展實際的北極戰略作為。俄羅斯作為最大的北極國家，在北極坐有得天獨厚的地緣優勢。在2020年發布的《俄羅斯聯邦2035年前及長期遠景的國家北極政策基礎》中，俄方將開發北極資源與維護國家安全列為北極事務中的最優先目標，而俄烏戰爭的發生，卻嚴重影響了俄羅斯的北極戰略，更是促使其重新思考北極戰略走向的一大變因。中國方面，作為最有力的非北極國家之一，在2018年公布的《中國北極政策白皮書中》中，首次將自己定義為「近北極國家」，並強調中國是北極的「重要利益攸關方」，並將以「不越位，不缺位」的態度參與北極事務，復又加深了北極政治的複雜性。\n俄中同為執國際事務牛耳的大國，在北極的互動淵遠流長，而俄中的北極戰略，更是牽動北極地緣政治走向的影響因子。然而，同受於北極地緣政治驅動力的俄羅斯與中國，卻產生了相異的北極地緣政治觀，而俄中的北極戰略，也進而呈現出相異的戰略目標與地緣政治上的意涵。隨著北極議題的矚目度逐年上升，不僅政策制定者積極尋求北極地緣政治上的機遇，研究者也相當關切北極的國際關係互動與地緣政治走向。 As the intensification of the greenhouse effect continues, the world is facing unprecedented new climates. With the annual melting of Arctic Sea ice, it implies that the Arctic Ocean could become fully navigable between 2040 and 2060, revealing a significant geopolitical value that national actors cannot ignore. After the millennium, countries gradually realized the immense geopolitical impetus of the Arctic. Not only are Arctic nations vigorously developing the region, but non-Arctic countries are also attempting to participate in Arctic affairs, gradually elevating the political significance of Arctic issues and affairs.\n\nThe purpose of this article is to use geopolitics theory as a starting point to deeply compare the similarities and differences in the Arctic strategies of the Russian Federation and the People`s Republic of China. Russia and China, as Arctic and non-Arctic countries respectively, have each issued a series of national Arctic policies and are actively pursuing practical Arctic strategies. Russia, being the largest Arctic country, holds unique geographical advantages in the region. In its 2020 “Basic Principles of the State Policy of the Russian Federation in the Arctic for the Period up to 2035 and Beyond,” Russia prioritizes the development of Arctic ...